2020
DOI: 10.1111/sum.12684
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of spectral pre‐processing for estimating soil condition on small farms

Abstract: The concepts of soil security (especially relating to soil condition) provide a useful framework in building spectral libraries. Spectral libraries can be used with the purpose of assessing soil condition by measuring soil organic carbon (SOC) or increasing productivity through soil nutrient management. A spectral library was generated by measuring SOC and nutrients (nitrogen, phosphorous and potassium) and spectral reflectance data over the visible to near-infrared range (350-2,500 nm) in soil samples collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…2) illustrates this finding by the different grouping of individual field datasets due to different pre-processing. This leads to the conclusion that studies that did not optimize the pre-processing scheme for every soil property separately did eventually not make full use of the spectroscopy potential (see also examples in Table 3), which has been shown by other studies as well (Alomar et al, 2021;Rodriguez-Febereiro et al, 2022;Singh et al, 2022). Nevertheless, the property-specific optimization of spectral pre-processing is a tedious process and constrains the fast and cost-effective application of vis-NIR spectroscopy, but some progress has been made simultaneously with our study by Mishra et al (2022).…”
Section: Pre-processingmentioning
confidence: 86%
See 1 more Smart Citation
“…2) illustrates this finding by the different grouping of individual field datasets due to different pre-processing. This leads to the conclusion that studies that did not optimize the pre-processing scheme for every soil property separately did eventually not make full use of the spectroscopy potential (see also examples in Table 3), which has been shown by other studies as well (Alomar et al, 2021;Rodriguez-Febereiro et al, 2022;Singh et al, 2022). Nevertheless, the property-specific optimization of spectral pre-processing is a tedious process and constrains the fast and cost-effective application of vis-NIR spectroscopy, but some progress has been made simultaneously with our study by Mishra et al (2022).…”
Section: Pre-processingmentioning
confidence: 86%
“…It has been shown that local models improve with increasing numbers of calibration samples and that a sample size of at least 50 provides accurate prediction models (Kuang and Mouazen, 2012). Some studies thus combined multiple target sites and develop a general model by combining all the local datasets to reach a larger sample size and potentially better model performance (Kuang and Mouazen, 2011;Singh et al, 2022). In these studies, the general model showed an intermediate performance, and the general prediction error was between the best and the poorest performing local model.…”
mentioning
confidence: 99%
“…2) illustrates this finding by the different groupings of individual field datasets due to different pre-processing. This leads to the conclusion that studies that did not optimize the preprocessing scheme for every soil property separately did eventually not make full use of the spectroscopy, which has been shown by other studies as well (Alomar et al, 2021;Rodriguez-Febereiro et al, 2022;Singh et al, 2022). Nevertheless, the property-specific optimization of spectral preprocessing is a tedious process and constrains the fast and cost-effective application of vis-NIR spectroscopy, but some progress has recently been made by Mishra et al (2022).…”
Section: Pre-processingmentioning
confidence: 96%
“…Kuang and Mouazen (2012) showed that local models improve with an increasing number of calibration samples and that a sample size of at least 50 provides accurate prediction models. Some studies thus combined multiple target sites and developed a general model by combining all the local datasets to reach a larger sample size and potentially better model performance (Kuang and Mouazen, 2011;Singh et al, 2022). In these studies, the general model showed an intermediate performance, and the general prediction error was between the best-and the poorest-performing local model.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of information, big data and relevant technology have the great potential of facilitating better understanding of agricultural available data. Remote sensing combined with laboratory analyses of samples could generate digital soil maps, building the farmland information system that will provide ready and efficient data‐driven planting strategy for smallholders (Piikki et al, 2020; Singh et al, 2020). Using the data to form soil indicators (other than merely judging by colour) or quick testing toolkits will make the evaluation of soil quality more precise and convenient (Mihoub et al, 2021).…”
Section: Anticipating Uncertainties With Technologymentioning
confidence: 99%